Mobile Attention Bias Modification Training Is a Digital Health Solution for Managing Distress in Multiple Sclerosis: A Pilot Study in Pediatric Onset - Charvet, Leigh; George, Allan; Cho, Hyein; Krupp, Lauren B.; Dennis-Tiwary, Tracy A. (Frontiers in Neurology, 2021)
Introduction: Emotional health is important dimension of care for patients living with pediatric onset multiple sclerosis (POMS), but few options are available for stress and anxiety reduction. The high burden of interventions requiring regular in person and onsite visits for treatment are less feasible. Attention bias modification training (ABMT) is effective for anxiety reduction in adult and adolescent populations. We tested the feasibility and preliminary efficacy of ABMT delivered through a mobile gamified version as a digital emotional health tool for patients with POMS. Methods: Participants with POMS were consecutively recruited from the NYU Langone Pediatric MS Care Center and enrolled to complete a 1-month intervention with use of the Personal Zen ABMT app on their mobile personal device. Feasibility was evaluated by use of the 1-month intervention and efficacy was measured by changes in depression, anxiety, and affect. Results: A total n = 35 patients with POMS were enrolled in the study (Mage = 17.7, SD = 2.2 years, range 14–23). Feasibility criteria were met with 74% completing the full intervention time, and 100% of the sample completing at least 50% of targeted intervention use. Initial efficacy was found for a reduction in negative affect from baseline to intervention end [M = 22.88, SD = 9.95 vs. M = 19.56, SD = 7.37; t(33) = 2.47, p = 0.019]. Anxiety also significantly decreased from pre to post-intervention in adults [M = 11.82, SD = 9.90 vs. M = 7.29, SD = 7.17; t(16) = 3.88, p = 0.001] and youth [M = 51.14, SD = 19.66 vs. M = 40.86, SD = 27.48; t(13) = 3.17, p = 0.007]. Conclusion: Mobile ABMT with the Personal Zen app is a feasible and accessible digital emotional health tool for patients with POMS and may have broader application for managing distress across chronic neurological conditions.